Identifikasi Type Human Papillomavirus (HPV) pada Penderita Kanker Serviks - Marlina Marlina; Yufri Aldi; Andani Eka Putra; Densi Selpia Sopianti; Dewi Gulyla Hari; Arfiandi Arfiandi; Akmal Djamaan; Rustini Rustini (Fakultas Farmasi Universitas Andalas, 2016)
Human Papillomavirus (HPV) is the most significant risk factor for the cause of cervical cancer. The purpose of this study for identification of HPV types 16, 18, 31, 33, 45 and 52 in cervical cancer patients. HPV is a row of high-risk HPV types that can cause cervical cancer. Total sample of 78 diisolat DNA derived from FFPE, cervical smears and cervical cancer fresh tissue obtained from Dr. Dr. M. Djamil, Padang and hospitals. Arifin Achmad, Pekanbaru. HPV DNA detection is done by using Polymerase Chain Reaction (PCR) using universal primers GP5 +/6 +. HPV types were identified by PCR with specific primers. Total sample types obtained with concentrations varying between 0.9 to 645 ng / ml with purity DNA in accordance with the specified purity for PCR amplification. The results of the study of 78 patients with cervical cancer samples, 42 samples (54%) identified HPV DNA. HPV type 18 is more dominant and followed by HPV type 16 as compared to the other types, namely the percentage of 40.4% and 28.5%. HPV type 45 (7.1%), HPV type 52 (2.3%) and HPV 31 and HPV type 33 was not detected.